There it is—the idea: justice as utopia: Fredric Jameson, in memoriam - Zamora-Sauma, Rocío (2025)
In tribute to Fredric Jameson, a few months after his passing, this article explores the social function of utopia in his thought, in dialogue with practices of transitional justice in Guatemala –particularly the Ixil Trial and the testimony of one of its witnesses, Ana de León López. The article argues that, despite the decline of the great revolutionary utopias of the twentieth century, alternative forms of utopian imagination endure. It suggests that certain processes of transitional justice, such as the Guatemalan case, can be understood as sites where the utopian imagination is constructed and reactivated in the sense proposed by Jameson. In these instances, utopia re-emerges from lived experience and from the desire for historicization and justice.